The Impact of The Service Quality of The Cleaning Staff of The Depot Logistics Employee Cooperative in The Servqual Model on Consumer Satisfaction at The East Nusa Tenggara Regional Office of Perum Bulog - Ludji Pa, Pieter Alexander; Kabanga, Margaretha S.; Manongga, Irience R. A. (Journal of Practical Management Studies, 2025)
In the era of globalization and increasingly fierce market competition, companies are racing to increase customer loyalty by focusing on service quality. Customer satisfaction is key to success, measured by perceptions of expectations influenced by objective quality and subjective interactions. Good service quality creates positive perceptions, satisfaction, and loyalty. Service quality indicators include physical evidence, empathy, reliability, responsiveness, and assurance. The theory used is from Tjiptono and Chandra (2016), expected service and perceived service. According to Husein Umar, quoted from his book Business Feasibility Studies (2005), "Customer satisfaction is the level of feeling a customer has after comparing what they receive with their expectations." This research uses a quantitative method with a survey. Data were analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination with the help of SPSS 30. The research results partially show that service quality in the form of physical evidence (t-count -0.045; Sig. 0.965), empathy (t-count 10.063; Sig. 0.550), and assurance (t-count 0.138; Sig. 0.891) have no significant effect because t-count < t-table (2.023) and Sig. > 0.05, while reliability (t-count 2.227; Sig. 0.032) and responsiveness (t-count 2.454; Sig. 0.019) have a significant effect. The F-test shows that all five variables have a significant combined effect (F-count 27.471; F-table 2.619; Sig. <0.001b) with an R² of 0.755, or 75%.